The Tragedy of Trafficking of Women and Children. Issue 1 (January 2019) - Callister, Lynn Clark
Abstract : Most victims of human trafficking are women and girls. Our global health nursing expert, Dr. Callister, discusses the most recent evidence and how nurses can play an important role in identifying victims and helping them escape to safety.